Academic English Socialization Through Individual Networks of Practice. Issue 2 (27th August 2014) - Zappa‐Hollman, Sandra; Duff, Patricia A.
<x xml:space="preserve">Abstract</x> This article introduces the notion of individual network of practice (INoP) as a viable construct for analyzing academic (discourse) socialization in second language (L2) contexts. The authors provide an overview of social practice theories that have informed the development of INoP—community of practice (CoP; Lave & Wenger, 1991; Wenger, 1998) and social network theory (Milroy, 1987)—and review relevant literature on academic discourse socialization and more general L2 learning studies that have used either CoP or social network as theoretical frameworks. Next, they illustrate how INoP was applied in a study that examined the academic English socialization of Mexican students at a Canadian university. Findings from the INoP analysis of three participants provide evidence of its rich potential for examining academic (discourse) socialization processes in other contexts and possibly using complementary forms of data analysis involving the analysis of interactional data. The authors suggest future applications of INoP in TESOL to help refine and validate this construct. Investigating the INoPs of other groups of English language learners in English‐medium institutions will help scholars, educators, and students better understand the often unseen but vital social processes that mediate learning and consider ways of maximizing the potential of social networks and practices for their own educational purposes.